2017
DOI: 10.1002/jor.23419
|View full text |Cite
|
Sign up to set email alerts
|

Development of arthrogenic joint contracture as a result of pathological changes in remobilized rat knees

Abstract: This study aimed to elucidate how rats recover from immobilization-induced knee joint contracture. Rats' right knees were immobilized by an external fixator at a flexion of 140° for 3 weeks. After removal of the fixator, the joints were allowed to move freely (remobilization) for 0, 1, 3, 7, or 14 days (n = 5 each). To distinguish myogenic and arthrogenic contractures, the passive extension range of motion was measured before and after myotomy of the knee flexors. Knee joints were histologically analyzed and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 48 publications
4
55
0
Order By: Relevance
“…4,56 Excessive active exercises or stretching might even aggravate the fibrosis and subsequent motion restriction. [57][58][59] Although the surgical treatment of joint stiffness can improve joint motion, there is an urgent need for a non invasive prophylactic or first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…4,56 Excessive active exercises or stretching might even aggravate the fibrosis and subsequent motion restriction. [57][58][59] Although the surgical treatment of joint stiffness can improve joint motion, there is an urgent need for a non invasive prophylactic or first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Joint contracture is characterized by loss of passive range of motion (ROM) and restriction of the activities of daily living, and is an important clinical problem in orthopedics and rehabilitation medicine. The most common cause of joint contracture is immobilization, which is a common orthopedic treatment for patients with severe traumatic injuries of the joints or other musculoskeletal disorders . In addition, several studies demonstrated that patients with conditions limiting their mobility are at a high risk for joint contracture .…”
mentioning
confidence: 99%
“…To clarify the fibrotic changes in the posterior joint capsules, we evaluated collagen density using the method described in our previous study. 4 In AFMG-stained sections, the posterior joint capsule was photographed just behind the meniscus at 20Â magnification with a light microscope (BX-51; Olympus, Tokyo, Japan) and a digital camera (DS-Fi1, Nikon, Tokyo, Japan) and analyzed with ImageJ software. Using the Split Channels function, the green areas, which represented collagen, were isolated from the original color image.…”
Section: Quantification Of Collagen Density In Joint Capsulementioning
confidence: 99%
“…Joint contracture, defined as a limitation in active and passive range of motion (ROM) on the affected joints, is a common complication of various nonphysiological conditions in joints of orthopedic patients, including neurological disorders, 1,2 prolonged immobilization, [3][4][5] and inflammation. [6][7][8] Restriction of ROM limits the performance of stable and functional movements and restricts activities of daily living in affected patients.…”
mentioning
confidence: 99%